DAMPAK SOSIAL DANA DESA DALAM KESEJAHTERAAN MASYARAKAT DI DESA KALOLA, KECAMATAN MANIANGPAJO, KABUPATEN WAJO - Andi Ashar; Andi Agustang (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2020)
This study aims to determine how the utilization of village funds and the social impact of village funds on community welfare in the village of Kalola, Maniangpajo District, Wajo Regency. The data obtained in this study used descriptive qualitative analysis. The technique of determining informants uses purposive sumpling or data collection by determining informant criteria, namely the Kalola villagers who have settled before and after the village funds. Data collection techniques used were observation, interviews and documentation. Descriptive type qualitative data analysis techniques through three stages, namely data reduction, data presentation, and drawing conclusions. The data validation technique is using member check. The results of this study indicate that 1) Utilization of village funds in the village of Kalola is divided into two, namely utilization through physical development and utilization through community empowerment. Physical development includes the construction of village infrastructure while the utilization of village funds through community empowerment. Physical development is 70% while community empowerment is 30%. 2) The social impact of village funds on community welfare in the village of Kalola is divided into 2 namely a. positive: The community can easily access the road to the rice fields, the poor feel satisfied, improve the standard of living of the community, the villagers have the skills. b. negative: The emergence of conflict between citizens, the erosion of integration between communities, the community is more concerned with personal interests, the crime that occurred in the village.